Calculate the following sum of series
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Define the function f ( x ) = n = 0 ∑ ∞ 4 4 n + 1 ( 4 n + 1 ) ( − 1 ) n x 4 n + 1 , where we seek f ( 1 ) and f ( 0 ) = 0 .
f ′ ( x ) = n = 0 ∑ ∞ 4 4 n + 1 ( − 1 ) n x 4 n = 4 1 n = 0 ∑ ∞ ( − 2 5 6 x 4 ) n = 4 1 1 + 2 5 6 x 4 1 (Geometric Series)
= > f ( 1 ) = f ( 1 ) − f ( 0 ) = ∫ 0 1 f ′ ( x ) d x = ∫ 0 1 4 1 1 + 2 5 6 x 4 1 d x
= ∫ 0 4 1 u 4 + 1 d u ( u = 4 x ) .
Now this integral can be solved using partial fractions
( x 4 + 1 = ( x 2 + 1 ) 2 − 2 x 2 = ( x 2 − 2 x + 1 ) ( x 2 + 2 x + 1 ) )
To get at last the value 4 2 ln 1 7 − 4 2 1 7 + 4 2 + 2 arctan 4 4 + 2 − 2 arctan 4 4 − 2 ≈ 0 . 2 5